2018
DOI: 10.1021/acsami.8b08722
|View full text |Cite
|
Sign up to set email alerts
|

Laser Sintering of Liquid Metal Nanoparticles for Scalable Manufacturing of Soft and Flexible Electronics

Abstract: Soft, flexible, and stretchable electronics are needed to transmit power and information, and track dynamic poses in next-generation wearables, soft robots, and biocompatible devices. Liquid metal has emerged as a promising material for these applications due to its high conductivity and liquid phase state at room temperature; however, surface oxidation of liquid metal gives it unique behaviors that are often incompatible with scalable manufacturing techniques. This paper reports a rapid and scalable approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
205
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(205 citation statements)
references
References 62 publications
0
205
0
Order By: Relevance
“…LM offers a brilliant solution toward the settlement of these drawbacks, yet LM‐based electronics suffer from corrosion at the contact between liquid metal and metal. In recent years, various strategies have been explored to develop corrosion resistant coatings for flexible electronics and to improve the LM patterning techniques on soft substrates . Dickey and Franklin et al reported the use of printed carbon nanotubes as flexible electrode and interconnect material, which was used in conjunction with EGaIn to form reliable thin‐film transistors (TFTs).…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…LM offers a brilliant solution toward the settlement of these drawbacks, yet LM‐based electronics suffer from corrosion at the contact between liquid metal and metal. In recent years, various strategies have been explored to develop corrosion resistant coatings for flexible electronics and to improve the LM patterning techniques on soft substrates . Dickey and Franklin et al reported the use of printed carbon nanotubes as flexible electrode and interconnect material, which was used in conjunction with EGaIn to form reliable thin‐film transistors (TFTs).…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
“…The tangled CNTs on the surface can suppress the crack generation during the stretching process, facilitating the development of stretchable LM–solid metal contacts and circuits. Furthermore, LM nanoparticles (LMNPs) can be patterned to form complicate planar geometries using a modulated pulse laser irradiation process, followed by transplantation of the pattern to the desired substrates . Pulsed laser irradiation plays a pivotal role in triggering the rupture and evaporation of the LMNPs to form uniform solid–liquid biphasic conductive layer.…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…LM nanorod was also prepared and employed as a swimming nanomachine to drill into cancer cells and then transfer into a droplet for photothermal therapy . Moreover, deformable LM nanodroplets were applied as mechanically sintered or laser‐sintered conductive inks for flexible and stretchable electronics . By applying low forces or exposing to a focused laser beam, the LM nanodroplets were ruptured and the low‐viscosity LM was released.…”
mentioning
confidence: 99%
“…For instance, Hohman et al generated LM nanodroplets by sonication of bulk LMs in ethanol and stabilized by different surfactants including 1‐dodecanethiol, 3‐mercapto‐N‐propionamide, and polyvinylpyrrolidone (PVP) . This approach has been well‐studied and the resulting colloidal solution was employed as conductive ink for soft and flexible electronics . Stable aqueous suspensions of LM nanodroplets are not only for electronic applications, but also exhibit great potential in medicine and therapy, such as drug delivery, photothermal therapy, and bioimaging .…”
mentioning
confidence: 99%